Development of a PBL-Based Mushroom Material E-Module for Biology Learning Class X SMA - Siti Zumrotul Muafiah; Irsadi, Andin (Journal of Biology Education, 2024)
The learning process in the classroom is centered on the teacher and uses the lecture method, causing students to be less interested in following the learning process, and making students less active during learning. And students have difficulty understanding the material on the human reproductive system. This study aims to determine the feasibility and effectiveness of e-modules based on problem-based learning on mushroom material to improve the learning outcomes of high school students. This study uses a Research and Development (RnD) approach that has been modified into 8 steps of development and research consisting of, namely potential and problems, data collection, product design, design validation, design revision, product trials, product revisions, final products. The subjects of this study were students of X7 MA Riyadlotut Thalabah. The results of the validation of the Material Expert on the product were 81.71% (very feasible), and 95% (very feasible) from the Media Expert. The teacher's assessment obtained a percentage of 95.04% (very feasible). The results of the responses from 35 students of class X7 MA Riyadlotut Thalabah obtained an average of 93.68% (very feasible). The percentage of classical completion of MA Riyadlotut Thalabah students from the pretest was 25.71% and the posttest was 85.71%. And 71.42% of students got a range of medium to high N-gain values. Based on the research data, it can be concluded that the PBL-based mushroom E-module is feasible and effective in improving the learning outcomes of high school students.